(3JShjb GdNOeGJ (B:s (3eONd GSJQGJjLj(B.(3hXjaj(B.(3JWHjbj (B/s - (3GdYdGb, HTjQ YHGSs ((3YeGf(B: s (3OGQ RgQGf(B, s, 2001)
(3eONd Edi GdNOeGJ,GdNOeI GdLhgQ hGdNOeGJ GdJcejdjI GdOGYeI,GdeRjL GdJShjbj ddNOeGJ,OhQI MjGI GdefJL,JMOjO ecGfI GdNOeI aj GdShb,CfXeI GdNOeGJ,GdESJQGJjLjGJ GdOGYeI dCfXeI GdNOeI,JUeje GdNOeI,GHJcGQ hJWhjQ GdNOeGJ GdLOjOI,EOGQI GdWdH Ydi GdNOeGJ,LhOI GdNOeI GdeOQcI hQVG GdeSJajO,JSYjQ GdNOeGJ,JhRjY GdNOeGJ,JQhjL GdNOeGJ,GdJShjb GdOGNdj,GdeTcdGJ GdeJQJHI Ydi JShjb GdNOeGJs
Keywords: (3GdJShjbs